1995
DOI: 10.1523/jneurosci.15-05-03808.1995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine depletion on the morphology of medium spiny neurons in the shell and core of the rat nucleus accumbens

Abstract: Nucleus accumbens receives a dense dopaminergic innervation which is important in regulating motivated states of behavior such as goal- directed actions, stimulus-reward associations and reinforcement of addictive substances. The shell and core territories of this nucleus each receive functionally and morphologically distinct dopaminergic inputs and lesions of the ascending pathways totally deprive the core but not the shell of dopaminergic fibers. Medium spiny neurons are the principal targets of dopaminergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 64 publications
(59 reference statements)
12
71
1
1
Order By: Relevance
“…This possibility is supported by studies showing that Acb medium spiny neurons are structurally plastic. Dopamine depletion, psychostimulants and dyskinesia are all known to alter spine density and dendritic branching in Acb dendrites (Meredith et al, 1995;Robinson and Kolb, 1999;Meredith et al, 2000). In our study, however, less than one hour elapsed between AS and processing of brain tissue, and most reported changes in dendritic architecture occur after chronic manipulations.…”
Section: As-induced Changes In Dendritic D1r Distribution In the Acb mentioning
confidence: 53%
“…This possibility is supported by studies showing that Acb medium spiny neurons are structurally plastic. Dopamine depletion, psychostimulants and dyskinesia are all known to alter spine density and dendritic branching in Acb dendrites (Meredith et al, 1995;Robinson and Kolb, 1999;Meredith et al, 2000). In our study, however, less than one hour elapsed between AS and processing of brain tissue, and most reported changes in dendritic architecture occur after chronic manipulations.…”
Section: As-induced Changes In Dendritic D1r Distribution In the Acb mentioning
confidence: 53%
“…In contrast, the filopodium density was lower for analogous neurites on PCY (1.38 Ϯ 0.707 filopodia per 10-m neurite). Low dopamine levels are known to cause a reduction of dendritic spine density in dopaminoceptive neurons (37). The higher filopodium density on PCD indicated that the catecholamine functional groups could induce unique responses in differentiated PC12 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, changes in Cdk5 activity within nerve terminals of NAc could alter neurotransmitter release that, in turn, could change spine density. Dendritic spines are highly responsive to fluctuations in dopaminergic and glutamatergic transmission (Meredith et al, 1995;Segal and Andersen, 2000;Robinson et al, 2001). Postsynaptically, Cdk5 can modulate D1/cAMP/PKA/DARPP-32 intracellular signaling and regulate NMDA receptor function (Bibb et al, 1999a,b;Li et al, 2001).…”
mentioning
confidence: 99%